The Effects Of Aerosol-Based Cell Delivery Technique On The Regeneration And Repair Of Airway Epithelium - ., Egi Kardia (2017)
Aerosol-based cell delivery is a potential therapeutic strategy to overcome the debilitating reparative capacity of trachea and lung following injury. The goal of this study was to determine the effect of aerosol-based airway epithelial cell (AEC) delivery on tracheal repair and regeneration, lung damage, and local inflammatory responses in the setting of acute lung injury (ALI) induced by tracheal brushing in rabbit. AECs were isolated from the trachea of New Zealand white rabbits. In vitro aerosol delivery was performed to assess the viability of the cells. Brushing-induced tracheal injury was performed in a rabbit model to develop ALI. One day following injury, exogenous BrdU-labelled AECs were aerosolized using the MicroSprayer® Aerosolizer into the injured airway.